Vitamin K1 and K2: Biochemistry, Clinical Significance, and Therapeutic Potential in Human Healt - Wycik, Michał; Szczupak, Michał; Modzelewska, Anna Maria (Quality in Sport, 2025)
Vitamin K, encompassing phylloquinone (K1) and menaquinones (K2), is essential not only for coagulation but also for various extra-hepatic functions. This review summarizes current knowledge on the biological roles, absorption mechanisms, clinical relevance, and therapeutic implications of vitamins K1 and K2, with particular emphasis on their functions beyond hemostasis. The analysis is based on a comprehensive review of peer-reviewed articles, clinical trials, meta-analyses, and cohort studies sourced from databases including PubMed, Scopus, Web of Science, and Google Scholar. Keywords such as “vitamin K1,” “vitamin K2,” “menaquinone,” “osteocalcin,” “vascular calcification,” and “neuroprotection” guided the selection of the most relevant and up-to-date publications. Both K1 and K2 are involved in the γ-carboxylation of vitamin K-dependent proteins, playing pivotal roles in bone metabolism, vascular integrity, and potentially neurological health. Emerging evidence supports their protective effects against fractures, arterial calcification, and cognitive decline. Moreover, vitamin K status appears to influence outcomes in patients with cardiovascular, inflammatory, and neurodegenerative conditions. Notably, K1 and K2 differ in their absorption profiles and tissue distribution, suggesting complementary physiological benefits. Clinical considerations such as drug interactions and tailored recommendations for vulnerable populations (e.g., neonates, pregnant women, elderly) underscore the importance of individualized approaches to vitamin K intake. In conclusion, vitamins K1 and K2 are integral to systemic health, far beyond their classical role in coagulation. A deeper understanding of their distinct functions and improved strategies for assessment and supplementation may contribute to effective disease prevention and health promotion. Further research is warranted to establish standardized guidelines for optimal vitamin K status across diverse populations.